Fluoride Chemistry in Tin Halide Perovskites. Issue 39 (24th July 2021) - Pascual, Jorge; Flatken, Marion; Félix, Roberto; Li, Guixiang; Turren‐Cruz, Silver‐Hamill; Aldamasy, Mahmoud H.; Hartmann, Claudia; Li, Meng; Di Girolamo, Diego; Nasti, Giuseppe; Hüsam, Elif; Wilks, Regan G.; et al.
Abstract: Tin is the frontrunner for substituting toxic lead in perovskite solar cells. However, tin suffers the detrimental oxidation of Sn II to Sn IV . Most of reported strategies employ SnF2 in the perovskite precursor solution to prevent Sn IV formation. Nevertheless, the working mechanism of this additive remains debated. To further elucidate it, we investigate the fluoride chemistry in tin halide perovskites by complementary analytical tools. NMR analysis of the precursor solution discloses a strong preferential affinity of fluoride anions for Sn IV over Sn II, selectively complexing it as SnF4 . Hard X‐ray photoelectron spectroscopy on films shows the lower tendency of SnF4 than SnI4 to get included in the perovskite structure, hence preventing the inclusion of Sn IV in the film. Finally, small‐angle X‐ray scattering reveals the strong influence of fluoride on the colloidal chemistry of precursor dispersions, directly affecting perovskite crystallization. Abstract : Fluoride chemistry in tin halide perovskites improves the crystallization process. Fluoride anions selectively coordinate and remove Sn IV and affect the colloidal properties in solution. This study describes the working mechanism of SnF2 and highlights the importance of solution chemistry for controlling crystallization and Sn II oxidation in tin halide perovskites.